Effect of preoperative injection of superparamagnetic iron oxide particles on rates of sentinel lymph node dissection in women undergoing surgery for ductal carcinoma in situ (SentiNot study). Issue 6 (6th March 2019) - Karakatsanis, A; Hersi, A-F; Pistiolis, L; Olofsson Bagge, R; Lykoudis, P M; Eriksson, S; Wärnberg, F; Nagy, G; Mohammed, I; Sundqvist, M; Bergkvist, L; Kwong, A; et al.
Abstract: Background: One-fifth of patients with a preoperative diagnosis of ductal carcinoma in situ (DCIS) have invasive breast cancer (IBC) on definitive histology. Sentinel lymph node dissection (SLND) is performed in almost half of women having surgery for DCIS in Sweden. The aim of the present study was to try to minimize unnecessary SLND by injecting superparamagnetic iron oxide (SPIO) nanoparticles at the time of primary breast surgery, enabling SLND to be performed later, if IBC is found in the primary specimen. Methods: Women with DCIS at high risk for the presence of invasion undergoing breast conservation, and patients with DCIS undergoing mastectomy were included. The primary outcome was whether this technique could reduce SLND. Secondary outcomes were number of SLNDs avoided, detection rate and procedure-related costs. Results: This was a preplanned interim analysis of 189 procedures. IBC was found in 47 and a secondary SLND was performed in 41 women. Thus, 78·3 per cent of patients avoided SLND ( P < 0·001). At reoperation, SPIO plus blue dye outperformed isotope and blue dye in detection of the sentinel node (40 of 40 versus 26 of 40 women; P < 0·001). Costs were reduced by a mean of 24·5 per cent in women without IBC (€3990 versus 5286; P < 0·001). Conclusion: Marking the sentinel node with SPIO in women having surgery for DCIS was effective at avoiding unnecessary SLND in this study. Registration number: ISRCTN18430240 (http://www.isrctn.com ). Graphical Abstract: Sentinel lymph node dissection (SLND) is overperformed in ductal carcinoma in situ (DCIS) owing to lack of credible prognostic factors for invasion or when mastectomy is planned. In the SentiNot cohort study, marking the sentinel node with superparamagnetic iron oxide (SPIO) nanoparticles was shown to be an efficient way to spare unnecessary SLND procedures, with a good detection rate at reoperation and favourable effect in containment of incremental costs. SN, sentinel node; BD, blue dye. Nearly 80 per cent avoided node dissection